Предмет: Алгебра,
автор: MariaRils
3p(x-4)-p(3x), если p(x) = 4x+2
Ответы
Автор ответа:
0
p(x-4) = 4(x-4)+2 = 4x-14
p(3x) = 4(3x)+2 = 12x+2
3p(x-4) - p(3x) = 3*(4x-14) - 12x - 2 = -44
p(3x) = 4(3x)+2 = 12x+2
3p(x-4) - p(3x) = 3*(4x-14) - 12x - 2 = -44
Автор ответа:
0
Спасибочки!!!!
Автор ответа:
0
нез
Похожие вопросы
Предмет: Физика,
автор: abylkasymoverbol655
Предмет: Алгебра,
автор: wwwdanilaru18
Предмет: Информатика,
автор: fdusambaev
Предмет: Обществознание,
автор: gaymerok
Предмет: Обществознание,
автор: ор7ц83ецсрп7цц